1970
DOI: 10.3126/jpn.v1i2.5408
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology in a palpable breast lesion

Abstract: Background: Breast cancer is the common malignant lesion in women. Fine needle aspiration cytology has high sensitivity and specificity and is a simple, rapid and safe method to diagnose breast lesions. The aim of the study was to categorize breast lesions and correlate the Fine needle aspiration cytology diagnosis with histopatholoical findings. Materials and Methods:This was a retrospective study done in department of Pathology of Institute of medicine, Trivuwan university teaching hospital, from January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…[2,4,5,6,7,8,9] Proof of malignancy is the usual aim of such a procedure although it can be used for diagnosis of benign lesions as well as some inflammatory conditions. [5,7,8] The present study comprised of 529 aspirations performed on 512 patients. In 17 cases (3.2%), a second pass was needed, as the material was inadequate in the first instance.…”
Section: Resultsmentioning
confidence: 99%
“…[2,4,5,6,7,8,9] Proof of malignancy is the usual aim of such a procedure although it can be used for diagnosis of benign lesions as well as some inflammatory conditions. [5,7,8] The present study comprised of 529 aspirations performed on 512 patients. In 17 cases (3.2%), a second pass was needed, as the material was inadequate in the first instance.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies from Nepal have found fibrocystic change as the most common breast lesion. 13,14 While other studies from Nepal have found fibroadenoma as the most common breast lesion. 15,16 Studies from Lahore, Aurangabad and Mumbai have found fibroadenoma as the most common breast disease.…”
Section: Discussionmentioning
confidence: 89%
“…In all studies from Nepal, fibroadenoma was found as the most common benign neoplasm. [13][14][15][16] And as already mentioned, the neoplasm has been found to be even more common than fibrocystic change in some of those studies. 15,16 In the developed countries, carcinoma of breast is the most common non-skin malignancy in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that inflammatory and non proliferative breast diseases do not increase risk of cancer [1]. However, proliferative breast diseases with or without atypia confers mild and moderate risk respectively, whereas carcinoma in situ is associated with substantial risk of life if left untreated [2].The carcinomas often have a poor prognosis due to high rate of local recurrence as well as metastasis, necessitating surgery in some cases adjuvant to chemotherapy [3].The canine mammary tumor (CMT) account for between 25 to 50 percent of all the tumors occurring in the canines [4][5][6] and are only second to skin tumors [7].…”
Section: Introductionmentioning
confidence: 99%